English teachers’ beliefs and practices in integrating digital literacy in the language classroom - Much Deiniatur; Bambang Yudi Cahyono; Francisca Maria Ivone; Johannes Ananto Prayogo (International Journal of Evaluation and Research in Education (IJERE), 2024)
This case study investigates teachers’ beliefs (i.e., behavioral, normative, and control beliefs) and practices in integrating digital literacy in English as foreign language (EFL) classroom. A descriptive study on EFL teachers is used in this research. Four participants were purposively selected to give sufficient information to answer the research questions. Data from the participants were collected by using interviews, observation, and documentation. In terms of the teachers’ beliefs, the finding shows that the behavioral belief was related to the benefits of using digital literacy; normative belief dealt with the expectation in the social context of both superiors and peers; while control belief was about the availability of particular digital technology to be implemented in the classroom and the ability of teachers. With regard to the teachers’ practices, it was found that the teachers used several digital tools for searching for information, communication, collaboration, creativity, critical thinking, cultural understanding, and e-safety. It was evident that teachers’ strong beliefs in integrating digital literacy influence the implementation of digital literacy in the classroom. The findings of this study highlight the importance of cultivating teachers’ beliefs toward the actual implementation of the integration of digital literacy in the EFL classroom.